PERANCANGAN VIDEO IKLAN PRODUK HIJABSANIA - Raizal Shanisyahmi Al Akhyar; Ahmad Khoirul Anwar; Yudi Wibowo (Akademi Seni dan Desain Indonesia Surakarta, 2024)
Changes from time to time, especially now which has entered the modern era. This influences the way of dressing from western culture which has an impact on Indonesian society whose majority religion is Islam. Nowadays, you can find many different styles of hijab in Indonesia. One of the MSMEs that focuses on selling hijab products is HijabSania. HijabSania promotes products only through social media platforms such as WhatsApp and Instagram. The problem experienced by HijabSania is a problem with the concept of the video it uploads on Instagram. Therefore, it is necessary to make efforts to solve the HijabSania problem. The solution offered is a promotional media design with a Cinematic Video concept. The video that will be shown contains concerns about anxiety when wearing the hijab so that products from HijabSania are the solution to these concerns. Using a qualitative design method by collecting data and interviewing HijabSania, they produced a design in the form of a cinematic video which was intended as a product promotion medium and was supported by several other supporting media. Keywords: Design, Product Advertising, Products, Hijab